La crisis socio económica, y su impacto en la calidad de vida de los niños del centro infantil San José y la intervención del trabajador social - Jiménez Ramos, Adriana Inés (2016)
The present work has been done because of the serious concern the problem of poverty that affects and influences negatively on the quality of life of children San Jose Center during the morning in the city of Loja, especially in with respect to the satisfaction of the basic needs that by law corresponds to childhood, but by factors of personal and social order those children cannot meet these basic needs. To do this, through the application of an appropriate methodology , and based on the overall objective was raised investigate that how poverty affects children in their quality of life within their family, also based on the objectives specific is based theoretical and scientifically categories of research problem in confrontation with the findings , through a rigorous analysis of all information , which you get to consider several factors of poverty affecting children in the " children's Center St. Joseph morning hours " in their home environment . As first Measuring the observation guide was used in addition to the notebook field, among others to collect better information required and subsequently used the interview guide and survey to collect important information for investigative work. The analysis based on the results of the investigation indicate that the majority of mothers of children Children's Center San Jose during the morning, cannot afford all the basic needs of their children, among them they are: education, health, housing and clothing being these very important basic needs for welfare, improvement and development of children, stressing that food is one of the needs that mothers say if to cover according to their economic situation. The findings indicate that mothers have an informal work and in some cases their husbands are workers or unemployed , jobs that do not pay good wages , have no access to social security and therefore there is no sustainable economic development for family, which does not allow a good quality of life for their children . 5 Factors such as: taxes currently set to citizens for goods and services does not allow mothers to undertake a stable business, also because mothers are mostly single mothers or separated from her husband where the head of household are the same, unemployment and low educational level of the family especially mothers of children, issues that directly affect their children's quality of life. Opposing discoveries by means of the application of an appropriate methodology, as first Measuring instruments the observation guide was used, besides the field notebook, among other to pick up in a better way the required information, as well as later on it was used, the interview guide and the survey to pick up important information for the investigative work. As conclusion one can say that the poverty is a serious problem that affects the children of the Infantile Center San José in morning schedule inside its home, by means of a sinnúmero of factors that don't allow a well-being and quality of life for its integral development. Finally, it is important that in the Infantile Center San José incorporates a complete and interdisciplinary working team, where it is part of this group the Social Trabajador/a, so that bigger contribution exists to the improvement and economic development of the homes of the children of Infantile Center San José in morning schedule, and for ende it occurs bigger execution to the rights of the same ones.